2022
DOI: 10.1007/s43615-022-00240-3
|View full text |Cite
|
Sign up to set email alerts
|

Without a Debate on Sufficiency, a Circular Plastics Economy will Remain an Illusion

Abstract: To tackle the “plastic crisis”, the concept of circular economy has attracted considerable attention over the past years, both by practitioners and scholars alike. Against this background, this article reflects from a political scientist’s point of view on key issues currently under discussion regarding the implementation of a circular plastics economy. To do so, the article covers issues raised at the 2021 edition of the Tutzing Symposion, an annual event organized by DECHEMA, the German Society for Chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The emission reduction effects in various countries generally exceed 20%, with Europe even achieving a reduction of up to 40%. These findings emphasize the importance of limiting consumer demand and the necessity of implementing appropriate policies to promote the circular economy [92]. Therefore, future policymakers and stakeholders should prioritize the importance of limiting consumer demand and actively take measures to achieve significant reductions in global greenhouse gas emissions, promoting global progress towards a more sustainable development direction.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The emission reduction effects in various countries generally exceed 20%, with Europe even achieving a reduction of up to 40%. These findings emphasize the importance of limiting consumer demand and the necessity of implementing appropriate policies to promote the circular economy [92]. Therefore, future policymakers and stakeholders should prioritize the importance of limiting consumer demand and actively take measures to achieve significant reductions in global greenhouse gas emissions, promoting global progress towards a more sustainable development direction.…”
Section: Discussionmentioning
confidence: 91%
“…In the analysis of resource metabolism indicators under 13 circular economy scenarios, it was found that as long as demand continues to grow-regardless of the levels of RR, CMUR, and CLCR-the VMC indicator shows an upward trend, sharply increasing with demand. Some studies have also found that reducing production and consumption is a prerequisite for achieving a truly circular plastic economy [92]. This finding emphasizes the importance of demand control; besides measures such as increasing recycling, reducing waste at the source is also crucial [93].…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, recently the concept of circular carbon economy based on biotechnological plastic recycling has become a thriving research area in recent years ( Ru, Huo, and Yang, 2020 ; Ellis et al, 2021a ; Kakadellis and Rosetto, 2021 ; Simon et al, 2021 ). In addition to the traditional mechanical recycling and chemical recycling ( Mederake, 2022 ), biocatalytic depolymerization catalyzed by PET-degrading enzymes (e.g., PETase) has emerged as a promising and sustainable alternative for PET upcycling and enable circularity ( Magalhães, Cunha, and Sousa, 2021 ; Cao et al, 2022 ; Lai et al, 2022 ; Ambrose-Dempster et al, 2023 ). A variety of naturally occurring plastic degrading enzymes have been discovered and characterized from microbial sources ( Kawai, 2021 ; Erickson et al, 2022 ; Khairul Anuar et al, 2022 ; Wei et al, 2022 ; Zhu, Wang, and Wei, 2022 ).…”
Section: Introductionmentioning
confidence: 99%